Crystal death : a Conor Bard mystery - Kipps, Charles (New York : Scribner, 2010)
N.Y.P.D Detective Conor Bard investigates the murder of Israeli diamond dealer Zivah Gavish in her Manhattan apartment. A priceless red diamond is missing, and the South African government is determined to find it. His new partner, Rosita Rubio, is at his side as the list of murder suspects grows quickly.
"Second installment in the Conor Bard mystery series" -- Dust jacket.
Keywords: Police -- New York (State) -- New York -- Fiction; Diamond industry and trade -- New York (State) -- New York -- Fiction; Murder -- Investigation -- New York (State) -- New York -- Fiction; Manhattan (New York, N.Y.) -- Fiction